Exchange Stock Price Prediction using Time Series data: A Survey - Ghous, Hamid; Malik, Mubasher H; Mahrukh, Ayesha; Zaffar, Abdul Mueed (Pakistan Journal of Humanities and Social Sciences, 2023)
Stocks, which are ownership shares in the company, can be issued and traded on the platform known as a stock exchange by publicly traded companies. A centralized marketplace is provided by a stock exchange where stocks can be traded by buyers and sellers coming together, thereby ensuring liquidity and price transparency. Large studies have been conducted for a long time in regions such as foreign exchange, stock prices, and weather reviews where time series forecasting information has been comprised. In our research work, we will use time series data because time series allows us to compare what elements have an effect on certain variables from time to time. The primary goal of this review paper is to provide a comprehensive overview of the research conducted by various scholars on predicting stock market prices using time series data. Evaluating time series data can provide valuable insights into the changes in a particular asset, security, or financial variable over time. Forecasting techniques using time series analysis are employed in both fundamental and technical analysis.